Perancangan Sistem Informasi Akuntansi Pembelian Pada PT Khomsah Khalifah Dengan Menggunakan Software PHP dan MySQL - Ajie Rizal Asari (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
PT Khomsah Khalifah addressing Jl. Walungan RT/04 RW/02 Kel.Cisataranten Kulon Kec.Arcamanik Kab.Bandung 40293. At PT Khomsah Khalifah in carrying out the process of recording the purchase transaction, the manual has not yet been used in the program. This problem results in ineffective and efficient performance of all the divisions contained in the company body to the provision of information and reports needed. For these problems the researchers took the title of the final project â€œDesigning Accounting Information Systems Purchasing at PT Khomsah Khalifah Using PHP And MySql Softwareâ€. The population used by the researcher is the purchase procedure of PT Khomsah Khalifah pata in 2015/2016 and the sample is the purchase procedure in 2015, the objek of the research conducted describes the purchasing procedure at PT Khomsah Khalifah, system development method that i use is waterfall. The results of the research that the author did was the purchase accounting information system software so that data processing and reporting of purchases at PT Khomsah Khalifah were expected to be computerized properly.